Psychosocial outcomes and coping after complete avulsion traumatic brachial plexus injury - Franzblau, Lauren; Chung, Kevin C (Disability and rehabilitation, 2015)
To understand psychosocial outcomes, coping and adjustment after complete avulsion traumatic brachial plexus injury (BPI). We conducted a grounded theory analysis of 12 semi-structured patient interviews exploring psychosocial outcomes, augmented by quantitative evaluation of self-reported mental health and social functioning, body image and coping strategies obtained via three questionnaires (SF-36, Brief COPE and modified SWAP). Subjects' main sources of psychological stress were chronic pain, unemployment, decreased self-efficacy and social-emotional consequences of poor body image. One third of participants reported depression, half experienced anger and frustration and two-thirds were dissatisfied with the appearance of their affected limbs. Acceptance, active coping, planning and emotional support were the most frequently used coping strategies. Patients encounter high levels of physical and psychological stress after complete avulsion BPI and must find ways to cope to adjust to their injuries. They face similar challenges to patients with spinal cord injuries, for whom many models describing coping and adjustment exist. Similar models could facilitate more complete adjustment and rehabilitation of BPI patients and help to reduce the prevalence of negative stress responses, including anger and depression. Future patients would benefit from a multidisciplinary treatment program, involving medical and mental health services.